THORNY PROBLEMS IN THE RUBIACEAE: BENKARA, FAGERLINDIA AND OXYCEROS - Ridsdale, C E (Research Center for Biology, 2008)
RIDSDALE,C.E.2008.Thorny problems in the Rubiaceae: Benkara,Fagerlindia and Oxyceros. Reinwardtia 12(4):289 â 298. â The shoot architecture of Fagerlindia and Oxyceros is discussed. Randia miquelii, Oxyceros rectispinaare transfered to â while Fagerlindia is reduced to a synonym of â Benkara. O. hoaensis are transferred to the genus Benkara. One new combination Oxyceros drupacea is made in the genus Oxyceros.